Peranan Pemberian Berbagai Dosis Pupuk Kascing untuk Meningkatkan Produktivitas Tanaman Mentimun Baby (Cucumis sativus L.) Secara Organik - Widodo, Andik; Qibtiyah, Mariyatul; Kusumawati, Dian Eka; Istiqomah, Istiqomah (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Cucumber is one of the most popular vegetable crops in the community. However, the production yield of cucumber plants is low. To increase cucumber productivity, there are steps that can be taken, namely by agricultural intensification. Intensification is a way to develop agricultural products that maximise the potential of existing land, one of which is through fertilisation. Fertilisation that is safe for the environment and health can be done through the application of organic systems. A very effective type of organic fertiliser is kascing, which is earthworm manure. This fertiliser is rich in nutrients that can be directly absorbed by plants, making it a good choice to accelerate the growth of cucumber plants. The purpose of the study was to examine the role of applying various doses of vermicompost fertiliser to increase the productivity of cucumber plants. The method used was RAK using 7 treatments with 4 replications. The treatments included variations in fertiliser dosage, namely no fertiliser; 2.5 t/ha; 5.0 t/ha; 7.5 t/ha; 10.0 t/ha; 12.5 t/ha; and 15.0 t/ha. The observations made consisted of, fruit weight per hectare, fruit weight per plot, fruit weight per sample plant, number of leaves, and plant height. The data obtained were calculated with the F test of 5% & 1% significance. If a significant difference is obtained, the next step is the 5% BNT test. The most optimal results due to the dose treatment of fertiliser kascing to increase the productivity of baby cucumber were obtained at the highest dose, which was 15.0 t/ha, compared to other doses